Making decisions to limit treatment in life-limiting and life-threatening conditions in children: a framework for practice - Larcher, V; Craig, F; Bhogal, K; Wilkinson, D; Brierley, J (BMJ Publishing Group, 2015)
In this extraordinary world of medical miracles, one thing has not changed; the complexity, challenge and pain of that most difficult of decisions: is the treatment we are providing no longer in the best interests of the child? There is no technology to help us here—only guidance, discussion, and adequate time and information for truly shared decision making. Our commitment to the child's best interests must start before birth and continue through to palliative and end of life care. Even after death, a duty to provide bereavement support for parents and siblings is the natural conclusion to the difficult decisions we have made with them in the preceding weeks and months. This latest guidance on arguably the most difficult aspect of paediatric care has updated the decision making framework and incorporated more extensive advice on the direct involvement of children and young people. It also takes account of the broader possibilities flowing from developments in paediatric palliative care.